The effect of the program for discovering and fostering Korea sports talents - Yoon, J. R.; Kim, H. J.; Lee, H. C.; Jo, J. Y.; Jo, I. H.; chang, D. K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In general, olympic athletes found their own performance at 8 to 12 years old through various programs. Furthermore, as it has reported that the program for discovering and fostering Korea Sports Talents has an effective influence on enhancement of athletic performance, the importance of the program development for young athletes at the national level has been emphasized. Therefore, the purpose of this study is to evaluate the effect of the program for discovering and fostering Korea Sports Talents by comparing records of the physical performance test(Basketball throw, Sit-up, Half Squat, Standing long jump, 20m Shuttle run, The 50m run, Sidestep, Seated forward flexion) before and after starting the program. Methods: The study subjects are 45 elementary school students (Age : 9.95years old ±1.44, Height : 143.65cm ± 11.84, Weight : 36.22kg ± 11.09) who have participated in 2015 Sports Talents Training Program. They were classified into a track and field training group (23 students), a swimming training group (12 students) and a gymnastics training group (10 students) and performed individual training (Track and field, Swimming, Gymnastics) twice a week for 3 hours a day for 6months. Results: Based on analysis of the basic physical performance test records before and after individual training, (1) those participated in a track and field training program showed a significant improvement in Basketball throw (t=-5.425, p<0.001), Sit-up (t=-2.814, p=0.01), Standing long jump (t=-4.595, p<0.001), 50m run(t=3.688, p=0.001) and 20m Shuttle run(t=-2.494, p=0.022). Those participated in a swimming program showed a significant improvement in Basketball throw(t=-11.238, p<0.001), Sit-up (t=-2.748, p=0.019). Those participated in a gymnastic training program showed a significant improvement in Seated forward flexion test (t=-2.712, p<0.024). Discussion: Consequently, the track and filed training program for discovering and fostering Korea Sports Talents is effective at improving muscular power, muscular endurance and cardiovascular endurance. The swimming training program is effective at improving muscular power, muscular endurance. The gymnastic program is effective at improving flexibility.